Litter Production of Enhalus acoroides and Thalassia hemprichii in the seagrass ecosystem of Tanjung Tiram, Inner Ambon Bay - Krisye Pasanea; Junita Supusepa; Amelia Putri (Politeknik Negeri Sambas, 2025)
Seagrasses are important primary producers that support marine life. The litter, or fallen leaves, of seagrasses plays a vital role as a source of nutrients in coastal ecosystems. One of the seagrass ecosystems found in Inner Ambon Bay is located in Tanjung Tiram. Studies on litter production have been extensively conducted in mangrove ecosystems; however, in the Maluku region, only one such study has been reported, and no research on seagrass litter production has yet been documented. Litter production serves as an important indicator for assessing coastal ecosystem functioning and blue carbon stocks. Therefore, this study aimed to analyze the litter production of two seagrass species, Enhalus acoroides and Thalassia hemprichii, in the Tanjung Tiram waters of Inner Ambon Bay. The research was conducted from July to August 2025 in the Tanjung Tiram seagrass ecosystem, Ambon City. Litter production was measured using the cage method, constructed from a 3 mm mesh nylon net with dimensions of 0.5 × 0.5 m. Prior to cage installation, the substrate was cleared of existing litter material and benthic organisms, and seagrass density was subsequently estimated. The study period lasted for 3 × 24 hours, with floating and sunken litter collected every 24 hours. The collected litter was oven-dried and weighed to determine dry biomass. Results showed that both E. acoroides and T. hemprichii produced higher amounts of sunken litter (0.0082 g dry weight/shoot/day and 0.0063 g dry weight/shoot/day, respectively) compared to floating litter (0.0062 g dry weight/shoot/day and 0.0028 g dry weight/shoot/day, respectively). The total litter production of E. acoroides (0.0144 g dry weight/shoot/day) was higher than that of T. hemprichii (0.0091 g dry weight/shoot/day).